DNA double strand break repair pathway choice in somatic mammalian cells - Scully, Ralph (Nat Rev Mol Cell Biol, 2019)
The major pathways of DNA double strand break (DSB) repair have key roles in suppressing genomic instability. However, if deployed in an inappropriate cellular context, these same repair functions can mediate chromosome rearrangements that underlie various human diseases, ranging from developmental disorders to cancer. Two major mechanisms of DSB repair predominate in mammalian cells, namely homologous recombination and non-homologous end joining. In this Review, we outline a ‘decision tree’ of DSB repair pathway choice in somatic mammalian cells, and consider how DSB repair dysfunction can lead to genomic instability. Stalled or broken replication forks present a distinctive challenge to the DSB repair system. Emerging evidence suggests that the ‘rules’ governing stalled fork repair pathway choice differ from those that operate at a conventional DSB.